Chapter 9 : Prototype Model Approach for Developing a Computed Tomography Scanner Application - M. S. M., Yusoff; R., Sulaiman; K., Shafinah; R., Fatihah; J., Abdullah (B P International, 2022)
The development of software applications for image reconstruction systems is critical in the computed tomography (CT) research study. An experimental prototype was the research tool used to create a series of useful prototypes for evaluating reconstruction methods. The prototype model approach has a short development period when developing an initial prototype for the user. A CT scanner software prototype was created using the MATLAB image processing toolbox together with the Graphical User Interface (GUI) and Graphical User Interface Development Environment (GUIDE). The prototype model was chosen to guide the development of the prototype application and, more importantly, to provide a platform for updating a system using existing knowledge. The prototype model was capable of creating synthetic CT scanner datasets, displaying a sinogram image from the synthetic datasets, constructing images using the back projection technique, and displaying cross-section images. This study yielded two kinds of images: unfiltered and blurry images and filtered and clear images. This study also concentrated on two-dimensional parallel-beam and fan-beam geometry configuration; the principle of transforming fan-beam datasets into parallel-beam datasets was implemented using the classic rebinning concept.